Analysis of Medical Records Personnel Needs Using the ABK KES Method - Yanti, Sri Yusni; Sari , Selvi Mayang; Sri Wahyuni (International Journal of Multidisciplinary Learners, 2025)
Burden Work type as much work as possible Possible must be resolved by a power Work health professional in One year there service health . Based on studies introduction at the Community Health Center Waborobo there are 4 officers consisting of 1 civil servant background behind D3 Nursing education, and 3 internships with background behind education 1 person D4 record medical, 1 person S1 public health and 1 D3 nursing person with total patient visits on in 2023 it will be 2,368. lack power record medical cause No orderly administration because Still obtained officer concurrently work others, like officer registration concurrently as officer screening And distribution as well as officer concurrently filing as officer registration. So that causes burden Work from officers more Lots . The aim of the research was to determine the need for medical records personnel at the Waborobo Community Health Center using the Health Workload Analysis (ABK Kes) method. This research applies a qualitative descriptive approach with a case study design. The object of the research is calculating the need for medical record personnel using the ABK Kes method. Data was collected through observation, interviews and documentation studies. The results of the research reveal that based on the calculations of the Kes crew, the available working time reaches 1,300 hours per year or 78,000 minutes per year in accordance with the lowest workload standard, namely distribution of 165,957, the standard of supporting tasks is 1.01 and the results of calculations according to the Kes crew's method show the need for manpower. medical records of 4 people. Waborobo Community Health Center already has 4 medical records officers, but there are several officers who do not meet the qualifications in accordance with applicable regulations.